PENGARUH PENGUKUSAN TERHADAP IMPREGNASI DENGAN BARAN PENGAWET CCA PADA KAYU RASAMALA (ALTINGIA EXCELSA NORONHA) - Barly Barly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
RQ8flmala ia one of a difficult timber species to be dried. The effect of steam conditioning before treatment on the impregnation 'Of green Bawn wood was investigated. This experiment shows that the different 1chedulesproduced different retentiori. Steaming before impregnation gave positioe effect on the treatability of green wood.